2012
DOI: 10.5114/ceji.2012.30792
|View full text |Cite
|
Sign up to set email alerts
|

Experimental immunology Influence of polysaccharide fraction C isolated from Caltha palustris L. on T and B lymphocyte subsets in mice

Abstract: Extracts from a diverse range of plants have been shown to possess immunomodulatory properties. Caltha palustris L. (Ranunculaceae) is a plant widely known and distributed in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The thymus index and spleen index could reflect the capacity of immunity [29]. As shown in Figure 1A,B, the spleen index and thymus index of the Cy group were significantly lower than those in NC group ( p < 0.01), which suggested that Cy had an effect on the weight reduction of immune organs.…”
Section: Resultsmentioning
confidence: 99%
“…The thymus index and spleen index could reflect the capacity of immunity [29]. As shown in Figure 1A,B, the spleen index and thymus index of the Cy group were significantly lower than those in NC group ( p < 0.01), which suggested that Cy had an effect on the weight reduction of immune organs.…”
Section: Resultsmentioning
confidence: 99%
“…The pectic polysacchariderich complex from Valeriana and Opilia celtidifola also stimulated the immune function of bone marrow cells and macrophage activity [15,17]. Polysaccharides fraction isolated from Ginkgo biloba folium has a good immunomodulatory activity rate [18], while fraction C from Caltha palustris extract can change the percentage and absolute number of T cell subsets in thymus, and T and B lymphocytes in the spleen and mesenteric lymph nodes [19].…”
Section: Discussionmentioning
confidence: 99%